Degradation of glass fibre reinforced polymer (GFRP) composite subjected to different environmental conditions - Mousay, Mohammed Mousay (2022)
Glass fibre-reinforced polymers (GFRPs) are composite materials that consist of glass reinforcing fibres embedded in polymer/plastic matrix such as epoxy, vinyl ester, or polyester resins. The matrix binds the glass fibres together, providing surface protection, and acting as a load transferring medium between the fibre elements while the fibre elements act as the main load-bearing component. The degradation of the GFRP in outdoor applications becomes a concern for many engineers and specialists. This concern becomes more critical when GFRPs are implemented to repair sensitive structures such as oil and gas pipelines and marine structures. Such structures can be found in harsh service environmental conditions. Several studies have investigated the degradation of FRP or GFRP composites in simulated conditions which might not fully reflect the real conditions while only limited studies have considered the impact of the actual weather conditions in a few countries. The degradation process under the actual conditions in these countries would be to some extent valid in their respective geographical location which might not be applicable to the other locations and conditions around the world. Malaysia is a tropical country with unique environmental conditions (heavy rain, high temperature, high humidity). Hence, the mechanical properties of GFRPs in these locations might be undergone specific degradations that are different from other location conditions in other countries. Therefore, this study aimed at determining the long-term impact of the natural ageing conditions in peninsular Malaysia on the mechanical property's degradation of GFRPs applications under three main environmental conditions which are atmospheric, underwater, and underground. It also aimed at examining the morphology of the specimens after the exposure to the above mentioned three field conditions. The GFRP samples were prepared using hand-layup fabrication technique from four layers of 0°/90° bi-directional woven E-glass fibre mats and epoxy resin and hardener (curing agent). The prepared samples were exposed in abovementioned three field conditions for four different exposure durations which are one, four, six, and nine months. Tensile test was used to evaluate the degradation behaviour of the GFRPs in the three environments. The findings revealed that the atmospheric environment has less influence on the GFRP strength capacity while underground and underwater environments cause a significant reduction in the tensile strength over the nine months of exposure. A total of 18%, 64% and 63% reduction in tensile strength was recorded for samples exposed to atmospheric, underground and underwater environments. Furthermore, the failure of the samples in the atmospheric environment shows partial failure in the matrix and fibres, while the underground and underwater show a lateral clean cut of the matrix and fibre. Scanning electron microscopy (SEM) results in the atmospheric environment exposure exhibited irregular fracture compared to the other environments. The nine-month SEM results for the underground and underwater environment exposure show that the failure of fibres and matrix was characterized by clean-cut failure. Furthermore, with only nine months, the trend of degradation is seen clearly with very high accuracy where the R2 more than 0.96. Overall, this study has a significant impact on understanding the long-term degradation behaviour of the GFRP composites in environments in Malaysia's tropical region. Further, it will increase confidence in implementing the GFRP composites in repairing and rectifying sensitive structures.